2010
DOI: 10.3844/jcssp.2010.934.939
|View full text |Cite
|
Sign up to set email alerts
|

Response of SAI Afferents May Play a Role in the Perception of Velvet Hand Illusion

Abstract: Problem statement:We revealed the reason behind a haptic illusion called the Velvet Hand Illusion (VHI) by FEM analysis. In VHI, a person rubs his/her hands together on both sides of wires strung through a frame and produces the sensation of rubbing a very smooth and soft surface like velvet. We focus on VHI to determine the specifications of an actuator for a tactile display enhanced by VHI. Approach: A simulated fingertip was modeled under the same contact condition that an actual finger was believed to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…They found that the strain energy is concentrated at the tactile receptor locations. A 2D FE fingertip model was also proposed by Chami et al to reveal the reason behind a haptic illusion called Velvet Hand Illusion (VHI) [10]. In addition, a 2D skin-receptor model combining an FE model of skin mechanics, a sigmoidal function of transduction, and a neural dynamics model was presented by Gerling et al to predict SA-I spike times in response to sustained indentation at the skin's surface [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that the strain energy is concentrated at the tactile receptor locations. A 2D FE fingertip model was also proposed by Chami et al to reveal the reason behind a haptic illusion called Velvet Hand Illusion (VHI) [10]. In addition, a 2D skin-receptor model combining an FE model of skin mechanics, a sigmoidal function of transduction, and a neural dynamics model was presented by Gerling et al to predict SA-I spike times in response to sustained indentation at the skin's surface [11].…”
Section: Introductionmentioning
confidence: 97%
“…Wu No. geometry geometry Viscosity behaviors [2] poor poor no no [3] poor fair no no 2D [9], [10] fair good no no [7], [8] poor fair yes yes [11] good good no yes [1] good fair no no 3D [12] fair fair no no [13] good fair no no into consideration to study the nonlinear and time-dependent force responses of fingertips during dynamic contact [6], [7], [8]. A 2D FE model of fingertip with detailed locations of various tactile receptors was proposed by Maeno et al to clarify the reason of the precise locations of these receptors [9].…”
Section: Introductionmentioning
confidence: 99%
“…The research in (Youssef and Peng, 2010) proposed a method that could deal with fault-tolerant control system by using the decentralized control theory. The study in (Chami et al, 2010) proposed a way that revealed the reason behind a haptic illusion called the Velvet Hand Illusion (VHI) by fem analysis. The research in (Alfred, 2009) presented the optimizing feature construction process for dynamic aggregation of relational attributes.…”
Section: Introductionmentioning
confidence: 99%